2015
DOI: 10.1016/j.immuni.2014.12.021
|View full text |Cite
|
Sign up to set email alerts
|

Enhancer Sequence Variants and Transcription-Factor Deregulation Synergize to Construct Pathogenic Regulatory Circuits in B-Cell Lymphoma

Abstract: Summary Most B cell lymphomas arise in the germinal center (GC), where humoral immune responses evolve from potentially oncogenic cycles of mutation, proliferation, and clonal selection. Although lymphoma gene expression diverges significantly from GC-B cells, underlying mechanisms that alter the activities of corresponding regulatory elements (REs) remain elusive. Here we define the complete pathogenic circuitry of human follicular lymphoma (FL), which activates or decommissions REs from normal GC-B cells and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
99
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(104 citation statements)
references
References 52 publications
4
99
0
1
Order By: Relevance
“…Interestingly, we did not observe overt changes of transcript levels driven by the top 2,000 RACK7 bound promoters in the RACK7 null cells (Figure S2J), suggesting RACK7 functions mainly at enhancers. Using an established, enhancer activity reporter assay (Koues et al, 2015; Outchkourov et al, 2013), we were able to confirm that 10 out of 10 candidate active enhancers bound by RACK7 and KDM5C indeed possess enhancer activities and most, if not all, of them are regulated by RACK7 and KDM5C (Figure S3). Together with the finding discussed in Figure 3, we conclude that RACK7 or KDM5C loss both lead to hyper-activation of these enhancers and higher transcriptional activities.…”
Section: Resultsmentioning
confidence: 79%
“…Interestingly, we did not observe overt changes of transcript levels driven by the top 2,000 RACK7 bound promoters in the RACK7 null cells (Figure S2J), suggesting RACK7 functions mainly at enhancers. Using an established, enhancer activity reporter assay (Koues et al, 2015; Outchkourov et al, 2013), we were able to confirm that 10 out of 10 candidate active enhancers bound by RACK7 and KDM5C indeed possess enhancer activities and most, if not all, of them are regulated by RACK7 and KDM5C (Figure S3). Together with the finding discussed in Figure 3, we conclude that RACK7 or KDM5C loss both lead to hyper-activation of these enhancers and higher transcriptional activities.…”
Section: Resultsmentioning
confidence: 79%
“…This approach led to the identification of genes with altered expression as a consequence of disrupted TF binding including several with known key roles in lymphomagenesis. Enhancer profiling by Koues et al in FL demonstrated that FL tumors not only suppress specific enhancers so as to shed nonessential components of the GC transcriptional circuitry but additionally hijacked critical enhancers from other lineages to acquire specific advantageous tumorigenic functions [66]. Taken together, these recent studies highlight the contribution of the noncoding genome future science group Epigenetic dysregulation in follicular lymphoma Special Report and earmark the importance of this exciting new chapter in FL pathogenesis.…”
Section: Noncoding Regulatory Regionsmentioning
confidence: 97%
“…For example, many disease-associated SNPs identified by genome-wide association studies are in the enhancer regions [44,51]. They can abolish known or create novelbinding motifs of transcription factors, thus altering their binding to enhancers [49,65]. Using ChIP-seq of H3K27ac and GATA3 transcription factor, Oldridge et al found that the risk SNP rs2168101 associated with neuroblastoma overlapped the GATA3-binding motif within the enhancer of LMO1 oncogene.…”
Section: H3k27ac and H3k4me1/2mentioning
confidence: 99%
“…Consistency of narrow peaks called from replicates can be assessed using the irreproducible discovery rate, by which high-quality peaks can be extracted at a user-defined irreproducible discovery rate cutoff (like 1%) [2]. The functionality of peaks can be validated through chromatin interaction analysis by paired-end tag sequencing or chromosome conformation capture (3C)-based chromatin interaction mapping methods [25,86], reporter assays [16,49,86] or using genomeediting tools like CRISPR (clustered regularly interspaced short palindromic repeats)/Cas9 [86]. Three major aspects of data analysis are critical for future success of ChIP-seq applications in the clinic.…”
Section: Key Experimental Considerationsmentioning
confidence: 99%
See 1 more Smart Citation